Al-Jedda v. Secretary of State for Defence (No 2). (2016) - Unknown
Abstract : 622 Jurisdiction — Justiciability — Actionability — Tortious activity — Immunity — Conflict of laws — Interpretation and application of foreign laws — Act of State Human rights — Right to liberty and security of person — Internment — Internment on suspicion of threat to security — Right to judicial review of detention — "Essence" of the right to liberty and judicial review of detention — Unlawful detention — Damages Relationship of international law and municipal law — Treaties — United Nations Charter, 1945 — European Convention on Human Rights, 1950 — United Nations Security Council Resolution 1546 (2004) — Coalition Provisional Authority ("CPA") — CPA Regulation 3 — CPA Regulation 17 — Iraqi Transitional Administrative Law or Interim Constitution — Iraqi Constitution — United Kingdom Private International Law (Miscellaneous Provisions) Act 1995 — Whether detention of appellant unlawful under Iraqi law — Whether relevant Iraqi provisions inconsistent with international law State responsibility — Occupation of Iraq — Multinational Force in Iraq — Vicarious liability — Defences — Act of State — Public policy — Relevance of nationality of person against whom act of State pleaded War and armed conflict — Occupation — Iraq — End of occupation — Powers of belligerent occupant — Internment — Fourth Geneva Convention, 1949 — Security Council Resolution 1546 (2004) — The law of England